Thyroid gland invasion in total laryngectomy and total laryngopharyngectomy: a systematic review and meta‐analysis of the English literature. (24th October 2013) - Kumar, R.; Drinnan, M.; Robinson, M.; Meikle, D.; Stafford, F.; Welch, A.; Zammit‐Maempel, I.; Paleri, V.
Abstract : Background: Advanced laryngeal and hypopharyngeal squamous cell carcinomas carry an inherent risk of invading thyroid parenchyma leading to the incorporation of a hemithyroidectomy or total thyroidectomy as part of a total laryngectomy. In some centres, thyroid gland removal occurs routinely during surgery for T3 and T4 laryngopharyngeal carcinoma. However, the incidence of invasion is low, and therefore, thyroid‐sparing surgery must be considered for select cases. Objective of review: The primary goal of the review is to assess the true incidence of thyroid gland invasion in laryngopharyngeal carcinoma. Utilising this data we aim to identify risk factors and clinical predictors of thyroid gland invasion to facilitate in a more targeted approach in the surgical management of advanced laryngopharyngeal carcinoma. Type of review: A systematic review and meta‐analysis of all published data and review of case series at Newcastle upon Tyne Hospitals (NuTH). Search strategy: MEDLINE (1946–2012) and EMBASE (1980–2012) were searched. Evaluation method: A single reviewer conducted the systematic review with a follow‐up ancestry search. Studies publishing case series of T3 and T4 laryngeal and hypopharyngeal carcinoma treated by total laryngectomy or laryngopharyngectomy and partial or total thyroidectomy, with pathological assessment for thyroid gland invasion rates were selected. Articles published prior to 1977 were excluded due to the advent of whole organ sectioning. Results: The literature search identified 16 studies suitable for inclusion, with 1180 cases. The NuTH case series identified 107 patients. The overall pooled incidence of thyroid gland invasion in 1287 patients is 10.7% (95% CI 7.6–14.2). Patients with primary subglottic tumours (relative risk 7.5; 95% CI 4.3–13.0) and disease extension into the subglottis (relative risk 4.3; 95% CI 2.5–7.2) have a significantly higher relative risk of thyroid gland invasion. Radiorecurrent tumours and hypopharyngeal tumours did not have an increased risk of thyroid gland invasion. Conclusion: Advanced laryngeal and hypopharyngeal carcinomas involving the subglottis carry a significantly elevated risk of thyroid gland invasion compared with those that spare this subsite. The overall incidence of thyroid gland invasion is low, and therefore, thyroidectomy should be reserved for cases considered to be at risk as opposed to a being a routine measure for all total laryngectomies.